Homemade fenestration and chimney techniques for the left subclavian artery revascularization during zone 2 thoracic endovascular aortic repair - Ye, Jiacheng; Li, Yuliang; Lu, Yue; Wang, Yongzheng; Liu, Bin; Chang, Haiyang (Frontiers in Cardiovascular Medicine, 2023)
Background To investigate the safety and efficacy of homemade fenestration and chimney techniques for the left subclavian artery (LSA) revascularization during zone 2 thoracic endovascular aortic repair (TEVAR). Methods From February 2017 to February 2021, 41 patients undergoing fenestration technique (group A) and 42 patients undergoing chimney technique (group B) to preserve the LSA during zone 2 TEVAR were enrolled in the present study. The procedure was indicated for dissections with unsuitable proximal landing zone with refractory pain and hypertension, rupture and malperfusion, and high-risk radiographic features. The baseline characteristics, peri-procedure, and follow-up clinical and radiographic data were recorded and analyzed. The primary endpoint was clinical success, and the secondary endpoints were rupture-free survival, LSA patency, and complications. Aortic remodeling, defined as patency, partial and complete thrombosis of the false lumen, was also analyzed. Results Technical success was achieved in 38 and 41 patients in groups A and B, respectively. Four intervention-related deaths were confirmed, two in each group. Immediate post-procedural endoleaks were detected in two and three patients in group A and B, respectively. No other major complications were found in either group, except for one retrograde type A dissection in group A. During follow-up, the initial clinical success rates were 90.24% and 92.86% in groups A and B, respectively. The primary and secondary mid-term clinical success rates were 87.5% and 90% in group A, and both of them were 92.68% in group B. Rupture-free survival and LSA patency were not significantly different between the two groups. The incidence of complete thrombosis in the aorta distal to the stent graft was 67.65% and 61.11% in groups A and B, respectively. Conclusions Apart from the lower clinical success rate of fenestration technique, both physician-modified techniques are available for LSA revascularization during zone 2 TEVAR and significantly promote favorable aortic remodeling.